2013
DOI: 10.1080/13506285.2013.807901
|View full text |Cite
|
Sign up to set email alerts
|

Anger superiority effect: The importance of dynamic emotional facial expressions

Abstract: A rapid response to a threatening face in a crowd is important to successfully interact in social environments. Visual search tasks have been employed to determine whether there is a processing advantage for detecting an angry face in a crowd, compared to a happy face. The empirical findings supporting the ''anger superiority effect'' (ASE), however, have been criticized on the basis of possible lowlevel visual confounds and because of the limited ecological validity of the stimuli. Moreover, a ''happiness sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 106 publications
(167 reference statements)
4
50
1
Order By: Relevance
“…In a previous study, which investigated the ASE under both static and dynamic conditions, we 8 indeed found evidence for an ASE when using dynamic displays of facial expressions, but not when the emotions were expressed by static face images (Ceccarini & Caudek, 2013).…”
Section: The Anger Superiority Effectmentioning
confidence: 55%
See 4 more Smart Citations
“…In a previous study, which investigated the ASE under both static and dynamic conditions, we 8 indeed found evidence for an ASE when using dynamic displays of facial expressions, but not when the emotions were expressed by static face images (Ceccarini & Caudek, 2013).…”
Section: The Anger Superiority Effectmentioning
confidence: 55%
“…Like in Experiment 1, the stimulus conditions of Ceccarini and Caudek (2013) are not optimal to study error reactivity after the failure to detect a threat. In fact, dynamic and static displays were randomly intermixed in half of the trials of their experiments, and an ASE was found for the dynamic displays only 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations